Implementación de un programa educomunicativo para la prevención de las demencias en Adultos Mayores. Centro Gerontológico Tierno Despertar Salinas. Periodo Noviembre 2023 – Marzo 2024 - Garcia Montoya, Evelyn Cristina (2024)
his research addresses the growing concern about dementia in the older adult population. In order to implement an educational-communicative program tailored to the specific needs of this population, we sought to provide detailed information on risk factors, early signs and symptoms of dementia, as well as strategies for prevention and management of the disease. The methodology adopted was descriptive and quantitative. The information was collected by applying surveys to family members and caregivers of older adults. To determine the prevalence of dementia in the Gerontological Center "Tierno Despertar", standardized tests such as the Mini-Mental Folstein test (MMSE) and the Montreal Cognitive Assessment (MoCA) were used. The results showed that a significant proportion of participants showed possible signs of cognitive impairment, with scores indicating varying levels of impairment in the tests applied. The program, which included interactive activities, visual materials and participatory methodologies, not only improved knowledge about dementia, but also encouraged the adoption of healthy and proactive habits. Furthermore, there was an improvement in communication and social interaction among older adults, which contributed to their emotional and cognitive well-being. In conclusion, these findings support the importance of educational interventions in the prevention and management of dementias in older adults. An educommunicative approach can significantly improve the quality of life and cognitive health of this population. Keywords: dementia, elderly, educommunication, prevention, cognitive health